Sistem Manajemen Order dan Pencatatan Keuangan Berbasis Website untuk Layanan Jasa Produk Digital di Startup - Irvan Pratama Putra; Kustiyono (LPPM Universitas Bina Sarana Informatika, 2026)
Digital product services in startups and small businesses still face many problems in order management and financial recording, which are carried out manually or using separate applications. This reduces work efficiency and increases the risk of recording errors and difficulties in monitoring order and financial status. This study aims to create an integrated web-based digital order management and recording system to assist in the management of digital product services. The research methods used were observation and interviews to analyze system requirements, while the system development method used the Waterfall model of the Software Development Life Cycle (SDLC). System testing was conducted using the black box testing method to ensure that all functions ran according to requirements. The results of the study show that the developed system is capable of improving the efficiency of order management and financial recording processes, as well as increasing data accuracy by minimizing recording errors and data duplication. The integration of order and financial data makes it easier for business owners to monitor work progress and financial conditions in real-time. Thus, this system can be an effective solution in supporting the management of digital product service businesses in a more structured and integrated manner.